MRI-Based Radiomics Nomogram for Selecting Ovarian Preservation Treatment in Patients With Early-Stage Endometrial Cancer - Yan, Bi Cong; Ma, Xiao Liang; Li, Ying; Duan, Shao Feng; Zhang, Guo Fu; Qiang, Jin Wei (Frontiers in Oncology, 2021)
Abstract Background: Ovarian preservation treatment (OPT) was recommended in young women with early-stage endometrial cancer with superficial myometrial invasion (MI) and grades (G) 1/2-endometrioid adenocarcinoma (EEC). A radiomics nomogram was developed to assist radiologists in assessing the depth of MI and in selecting eligible patients for OPT. Methods: From February 2014 to May 2021, 209 G 1/2-EEC patients younger than 45 years old (mean 39±4.3 years) were included. Of them, 104 retrospective patients were enrolled in the primary group, and 105 prospective patients were enrolled in the validation group. The radiomics features were extracted based on multi-parametric magnetic resonance imaging and the least absolute shrinkage and selection operator algorithm was applied to reduce the dimensionality of the data and select the radiomics features that correlated with the depth of MI in G 1/2-EEC patients. A radiomics nomogram for evaluating the depth of MI was developed by combing the selected radiomics features and the cancer antigen 125. Receiver operating characteristic (ROC) curves were used to evaluate the diagnostic performance of the radiomics nomogram, and of radiologists without and with the aid of the radiomics nomogram. The net reclassification index (NRI) and total integrated discrimination index (IDI) based on the total included patients to assess the clinical benefit of radiologists with the radiomics nomogram were calculated. Results: In the primary group, for evaluating the depth of MI, the AUCs were 0.94 for the radiomics nomogram; 0.80 and 0.86 for radiologists 1 and 2 without the aid of the nomogram, respectively; 0.92 and 0.94 for radiologists 1 and 2 with the aid of the nomogram, respectively. In the validation group, the AUCs were 0.89 for the radiomics nomogram; 0.82 and 0.83 for radiologists 1 and 2 without the aid of the nomogram, respectively; and 0.94 and 0.94 for radiologists 1 and 2 with the aid of the nomogram, respectively. The yielded NRIs and IDIs values were 0.23 and 0.31 for radiologist 1, 0.20 and 0.28 for radiologist 2, respectively. Conclusions: The radiomics nomogram outperformed radiologists and could help radiologists in assessing the depth of MI and selecting eligible OPTs in G 1/2-EEC patients.